Assessment of the pre-combustion carbon capture contribution into sustainable development goals SDGs using novel indicators. (January 2022) - Olabi, A.G.; Obaideen, Khaled; Elsaid, Khaled; Wilberforce, Tabbi; Sayed, Enas Taha; Maghrabie, Hussein M.; Abdelkareem, Mohammad Ali
Abstract: The rapid progress in the global population and technical advances have resulted in exponential growth in the use of fossil fuels. These are not only limited in resources but also have a severe environmental impact. The accumulation of greenhouse gases (GHGs), more specifically carbon emissions, in the environment has resulted in severe health issues and climate changes. The Paris Climate Agreement calls for restricting global warming to only 1.5 °C by 2050 relative to the pre-industrial era. This requires reducing global GHGs emissions as soon and as much as possible. Massive efforts are being put into minimizing GHG emissions, such as using renewable energy resources and/or using carbon capture technologies (CCT). In this study, different CCTs were introduced, focusing on the pre-combustion as a promising CCT approach. In this work, the role of CCT in realizing the United Nations Sustainable Development Goals (SDGs) was thoroughly analyzed and discussed. A total of 87 indicators were developed to measure and analyze the contribution of CCT to achieving the different SDGs. The focus given to the role of the pre-combustion CCT in achieving SDGs is being elaborated. The indicators and analysis covered the economic, environmental, and social pillars of sustainable development. It was found that CCT contributes well to all 17 SDGs, with core and substantial contributions to SDG-7 of "Affordable and clean energy", and ultimately SDG-13 of "Climate action". The developed indicators would work as a guideline for the different players to ensure that CCT is fully adhering the SDGs principles. The proposed indicators have nine main benefits, i.e., assist in the achievement of the SDGs, providing information for the decision-makers, enhance and benchmark sustainability performance, improve risk management, enhance data management and reporting practices, improve resource allocation and reduce the expenses, improve environmental performance, reduce social impact, and improve communications with stakeholder. Moreover, the different barriers facing the CCT were presented. Highlights: The role of the CCTs in achieving sustainable development and SDGs were presented. Develops a set of 87 novel indicators to assess the contribution of CCT into SDGs. Monitoring and evaluation of these indicators help to maximize CCT contribution to SDGs. The interrelation between CCT and circular economy with related SDGs were presented. The barriers facing the CCTs were elaborated and linked with SDGs.